Sheep Gait Biomechanics and the Assessment of Musculoskeletal Conditions: A Systematic Review - Silva, Rui (2019)
In recent years, sheep have been reported as the ideal animal model to study osteoporosis, hence it is important to identify instruments, tools and ideal parameters needed to assess the effects of different treatments. In previous studies conducted in other animal models with osteoporosis, the most common parameters used for evaluation concerned primarily bone properties, such as the dual X-ray absorptiometry. However, biomechanical gait analysis as an integrative functional parameter and a non-invasive method, will be an important tool in research and clinical applications. This research review was performed using the PubMed database and included studies related to sheep with outcome measures concerning functional performance assessed during gait in vivo; and excluded studies related with cardiovascular disease and sperm properties, which include other animal species, with outcomes not related with functional locomotor evaluation. Only studies related with bone properties were analyzed. The most frequent and relevant included parameters were the following: mean peak vertical ground force reaction, gait cycle and stance/swing phase duration, percentage of stance/swing phase in a gait cycle, stride length and the stifle joint angles during a gait cycle. Gait biomechanical parameters have been established for the assessment of some clinical orthopedic condition using sheep models but not currently for osteoporosis.